PENINGKATAN KETAHANAN TERHADAP RISIKO BENCANA MELALUI PENDIDIKAN KONSERVASI LAHAN BERBASIS MASYARAKAT DI DATARAN TINGGI DIENG - Indrayati, Ariyani (Jurnal Geografi, 2013)
The most important hazard problem at Dieng Plateu Region is land slide that giveintensive risk to the people especially who stay in the low land of the hilly land. Atthe other hand, land degradation happend very intensive and decreasing landfertility. Itâs happend because of land erotion and over intensive using ofchemistry product such as chemistry pestiside and fertilizar. That problem ismore seriously because the people do not understand or do not aware about landconservation. Awareness to land conservation have many purpose, in short timecan increasing land degradation, and in long time itâs means investation ineconomic meaning because of the sustainable land. The outcome of conservationawareness is ability to facing risk disaster. This research give the optionalconservation model based on community that have multi purposed, not onlyincreasing land quality but also stronger the community building to facing thedisaster risk.